MOTIVASI GURU DALAM PENDIDIKAN KARAKTER SISWA SD GMIM RANOLAMBOT KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA - REMBET, ALFIAN WENSI; RURU, JOORIE; PALAR, NOVIE (Sam Ratulangi University, 2018)
Motivation of teachers is one of the factors that determine student achievement. Because with the motivationof the teacher then grew a student's interest to continue to learn for the achievement of ideals in accordancewith what he wanted. Researchers see that there are problems in the performance of teachers in Primary SchoolGMIM Ranolambot, there are some teachers who are only graduates of SPG and have not been able to adjustwith teachers who graduated SI in the learning process or in the presentation of the material so that students'understanding is limited and the character of students is not formed, also in student discipline and in terms ofcare for the environment often children are not sensitive to the cleanliness that is in school and among thecommunity. The purpose of this paper is to know how Motivation Teachers In Education Character StudentGmim Ranolambot Elementary School District Kawangkoan West Minahasa District. This research isqualitative aimed at understanding social phenomena from the participant's point of view. The conclusion ofthe research result is the driving force in creating teacher motivation in SD GMIM Ranolambot SubdistrictKawangkoan Barat Minahasa Regency has not been achieved due to less motivated teachers from parents whoare less considerate; ways of shaping the skills that exist in the GMIM Ranolambot SD are poor because of thedifferent ways of teaching from dissenting teachers in terms of the use of methods and learning models; waysof shaping the skills of teachers are different, based on the circumstances and conditions of the students thatare not the same as different behaviors based on different family backgrounds; and some teachers are lessprofessional in the implementation of learning where they do not understand how to use methods pengajarangand learning models related to the material that has been prepared. From these conclusions, the authors provideadvice parents should provide support to teachers by giving attention to the child at home so it becomes theimpetus for teachers to keep trying to create students who have the knowledge and good character and someteachers should be professional by trying to learn selection of methods and models of learning. With so able toprovide quality learning for students.Keywords: Teacher Motivation, Student Character Education.